CRC handbook of basic tables for chemical analysis : data-driven methods and interpretation - Bruno, Thomas J.; Svoronos, Paris D. N. (Boca Raton : CRC Press, Taylor & Francis Group, 2020)
"Researchers in organic chemistry, chemical engineering, pharmaceutical science, forensics, and environmental science make routine use of chemical analysis, but the information these researchers need is often scattered in different sources and difficult to access. The CRC Handbook of Basic Tables for Chemical Analysis, Fourth Edition is a one-stop reference that presents updated data in a handy format specifically designed for use when reaching a decision point in designing an analysis or interpreting results. This new edition offers expanded coverage of calibration and uncertainty, and continues to include the critical information scientists rely on to perform accurate analysis"--
OCLC-licensed vendor bibliographic record.
Keywords: Chemistry, Analytic -- Tables; SCIENCE / Chemistry / Analytic; SCIENCE / Chemistry / Industrial & Technical